A high triplet energy small molecule based thermally cross-linkable hole-transporting material for solution-processed multilayer blue electrophosphorescent devices. Issue 2 (28th November 2014) - Jiang, Wei; Ban, Xinxin; Ye, Muyang; Sun, Yueming; Duan, Lian; Qiu, Yong
Abstract : A novel cross-linkable material with high triplet energy was synthesized to explore its use as a hole-transporting layer for efficient solution processed multilayer blue electrophosphorescent devices. Abstract : A novel cross-linkable hole-transporting material (HTM) has been synthesized and characterized. The HTM possesses high triplet energy, excellent film-forming and solvent-resistant abilities, suitable HOMO level and electrochemical stability. Solution processed multilayer blue electrophosphorescent devices using this cross-linked HTM show lower turn-on voltages and doubled efficiencies compared with the corresponding single-layer device.